Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the given system of equations:
[tex]\[ \left\{ \begin{array}{l} y = 6x - 11 \\ -2x - 3y = -7 \end{array} \right. \][/tex]
we will follow a systematic approach.
1. Substitute [tex]\( y \)[/tex] from the first equation into the second equation:
The first equation is:
[tex]\[ y = 6x - 11 \][/tex]
Substitute [tex]\( y = 6x - 11 \)[/tex] into the second equation:
[tex]\[ -2x - 3(6x - 11) = -7 \][/tex]
2. Simplify and solve for [tex]\( x \)[/tex]:
Distribute the [tex]\(-3\)[/tex] inside the parentheses:
[tex]\[ -2x - 18x + 33 = -7 \][/tex]
Combine like terms:
[tex]\[ -20x + 33 = -7 \][/tex]
Subtract 33 from both sides:
[tex]\[ -20x = -7 - 33 \][/tex]
[tex]\[ -20x = -40 \][/tex]
Divide both sides by [tex]\(-20\)[/tex]:
[tex]\[ x = \frac{-40}{-20} \][/tex]
[tex]\[ x = 2 \][/tex]
3. Substitute [tex]\( x = 2 \)[/tex] back into the first equation to find [tex]\( y \)[/tex]:
Using the first equation:
[tex]\[ y = 6x - 11 \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 6(2) - 11 \][/tex]
[tex]\[ y = 12 - 11 \][/tex]
[tex]\[ y = 1 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ (x, y) = (2, 1) \][/tex]
Among the given options, the correct solution is:
[tex]\[ (2, 1) \][/tex]
[tex]\[ \left\{ \begin{array}{l} y = 6x - 11 \\ -2x - 3y = -7 \end{array} \right. \][/tex]
we will follow a systematic approach.
1. Substitute [tex]\( y \)[/tex] from the first equation into the second equation:
The first equation is:
[tex]\[ y = 6x - 11 \][/tex]
Substitute [tex]\( y = 6x - 11 \)[/tex] into the second equation:
[tex]\[ -2x - 3(6x - 11) = -7 \][/tex]
2. Simplify and solve for [tex]\( x \)[/tex]:
Distribute the [tex]\(-3\)[/tex] inside the parentheses:
[tex]\[ -2x - 18x + 33 = -7 \][/tex]
Combine like terms:
[tex]\[ -20x + 33 = -7 \][/tex]
Subtract 33 from both sides:
[tex]\[ -20x = -7 - 33 \][/tex]
[tex]\[ -20x = -40 \][/tex]
Divide both sides by [tex]\(-20\)[/tex]:
[tex]\[ x = \frac{-40}{-20} \][/tex]
[tex]\[ x = 2 \][/tex]
3. Substitute [tex]\( x = 2 \)[/tex] back into the first equation to find [tex]\( y \)[/tex]:
Using the first equation:
[tex]\[ y = 6x - 11 \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 6(2) - 11 \][/tex]
[tex]\[ y = 12 - 11 \][/tex]
[tex]\[ y = 1 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ (x, y) = (2, 1) \][/tex]
Among the given options, the correct solution is:
[tex]\[ (2, 1) \][/tex]
-2x -3y = -7
-3y = 2x -7
y = -2/3x +7/3 (lets call this equation 1)
y = 6x -11 (lets call this equation 2)
Now, substitute equation 1 into equation 2.
-2/3x + 7/3 = 6x -11
-20/3x = -40/3
x = 2
Now, substitute x=2 back into equation 2.
y = 6(2) -11
y = 1
Hence the answer is D (2,1).
-3y = 2x -7
y = -2/3x +7/3 (lets call this equation 1)
y = 6x -11 (lets call this equation 2)
Now, substitute equation 1 into equation 2.
-2/3x + 7/3 = 6x -11
-20/3x = -40/3
x = 2
Now, substitute x=2 back into equation 2.
y = 6(2) -11
y = 1
Hence the answer is D (2,1).
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.